DESAIN ALAT PENGUBAH ARUS TEGANGAN DC MENJADI ARUS TEGANGAN AC DENGAN MENGGUNAKAN TRANSISTOR 2N3055 - Rahman, Rafiuddin; Lanto, Muhammad Said; Kadir, Ihsan (JFT : Jurnal Fisika dan Terapannya, 2014)
This research was conducted at the Department of Physics Laboratory instrumentation electronics, Faculty of Science and Technology, Alauddin State Islamic University (UIN) Makassar South Sulawesi. Formulation of research problems, namely (1) how to design transformers voltage DC voltage into AC current?, and (2) how much voltage and current is generated in transformers and DC voltage into AC?. In this study only uses transistor types (jengkol) with 2N3055 specifications. The results showed that (1) the design of transformers DC voltage into AC voltage current has been designed using 2N305 transistors to produce a form of inverters with 12 VDC input voltage and output voltage of 250 VAC. (2) The amount of voltage and current transformers resulting in a DC voltage into AC voltage currents generated before given input and output load currents.